"Man Up": Sex‐Differentiated Pathways of Juvenile Delinquency through Trauma, Borderline Traits & Offense Patterns. (26th August 2021) - McGill, Kathryn A.; Stefurak, Tres
Abstract: Juvenile delinquency presents a significant fiscal and moral cost to society; given the ability for early intervention and changing offending trajectories, it is essential to understand potential risk factors and offending patterns in justice‐involved youth. The current study examined features of 193 male and 96 female profiles on the Personality Assessment Inventory – Adolescent (PAI‐A) in conjunction with offending patterns to determine sex differences in offending. Significant sex effects on status offending were found for borderline and trauma symptoms. Contrary to hypothesized findings, higher borderline and trauma symptoms predicted more status offending for males, but not for females. Post‐hoc analyses postulate these findings showing males with higher frequency of status offending to also have higher rates of internalizing problems, as determined by PAI‐A scores. Results of this study can be implicated in better treatment of males in particular who have higher status offending, and help to broaden our knowledge of sex differences in juvenile offending.